Computational investigations of derivational morphology - Hofmann, V (2023)
The notion that it is difficult to make predictions about derivational morphology has been a recurring theme in morphological research over the last decades. It can be unclear whether a derivative exists at all, what a derivative means exactly, and which affix is used to form a derivative. The central goal of this thesis is to demonstrate that recent progress in natural language processing (NLP) allows for a fresh view on the (un-)predictability of derivational morphology.